Ataqlı dástanshı, baxshı Fazıl Yuldash ulı hám ol atqarǵan «Alpomish» dástanı haqqında - Turdımuratova, A.B (SCIENCE and SOCIETY, 2024)
The article discusses the Bulyngur school of storytellers and its famous representatives, who have a special role in Uz- bek epic studies, the biography and repertoire of bakhshi Fazil Yuldash uly, a famous narrator of heroic dastans, the last representative of the Bulungur school, the performance of the «Alpomish» dastan and recording, publication, as well as the conclusions of scientists on fulfillment of dastan.
Keywords: dastan; school of storytellers; epic; poetic; tradition; publication; heroic epic; genre; method; bakhshi; manuscript